THE EFFECT USE OF BIOSUPLEMENT CONTAINING PROBIOTIC BACTERIA OF CELLULOLYTIC TERMITES TO THE PRODUCTIVITY OF BALI DUCKS - LAKSMI DEWI M. P.; N. S. SUTAMA; G. A. M KRISTINA DEWI (Majalah Ilmiah Peternakan, 2018)
The research aims at analyzing the effect use of probiotic cellulolytic biosuplement termite (Termites sp.) tothe productivity of male bali ducks. Bacteria isolates used were first and second preeminent probiotic cellulolyticbacteria isolated derived from termites code BR3.3 and BR3.5. It was designed using a Completely RandomizedDesign with five treatments and three replicates consists of: basal ration without biosuplement (R0), ration basalwith biosupplement but without additional probiotic cellulolytic bacteria inoculant preeminent termites (RBCT0),RBCT1= basal ration with biosuplement probiotic cellulolytic bacteria inoculant preeminent termites 1, RBCT2=basal ration with biosuplement probiotic cellulolytic bacteria inoculant preeminent termites 2 and RBCT1-2= basalration with biosuplement probiotic cellulolytic bacteria inoculant preeminent termites 1 and 2. The result showedthat the initial body weight, slaughter weight and carcass percentage had no significant differences (P>0.05). Incontrast, final body weight, body weight gain, feed consumption, Feed Conversion Ratio and meat total cholesterolwere significantly affected (P<0,05) to the result. It can be concluded that use of basal ration supplemented withbiosupplement probiotic cellulolytic bacteria inoculant preeminent termites 2 (RBCT2) can increase productivity ofbali duck at the age of 2 up to10 weeks.